Planning Model of Integrated Livestock Area Based on Crop-Livestock Integration for Sustainable Rural Agribusiness Development in North Bolaang Mongondow District - Mujio; Purwanti, Sri; Lubis, Iskandar (Jurnal Ilmu-Ilmu Peternakan, 2025)
Rural agribusiness in Indonesia still faces inefficiencies due to the separation between the crop and livestock subsectors. This study developed a new Integrated Farming System (IFS) model by linking biomass circulation, spatial-functional planning, and village institutional strengthening within the framework of integrated livestock areas. A mixed-methods approach was employed, combining QGIS-based spatial analysis, economic evaluation (R/C ratio, profit margin, break-even point), and a SWOT-based institutional assessment. The analysis results showed the availability of approximately 41,000 tonnes/year of crop residues (rice, corn, and coconut) and 10,800 tonnes/year of beef cattle manure as inputs for a closed system. The implementation of the model has been proven to increase farming efficiency, with the R/C ratio increasing from 1.34 to 1.72, profit margins increasing by 26.7%, and the break-even point decreasing by 18%.  Theoretically, this study expands IFS research, which is generally limited to the household scale, by integrating it into a regional planning perspective through spatial-functional zoning and institutional strengthening. This contribution positions IFS not only as a technical system but also as a model for sustainable rural agribusiness planning. In practical terms, this study recommends the establishment of agribusiness cooperatives, capacity building for farmers, and cross-sector policy harmonization as key implementation strategies. This study uniquely integrates biomass-based IFS with spatial-functional planning and institutional design, thereby enriching both the theory and practice of sustainable rural development.